2021
DOI: 10.1002/advs.202102557
|View full text |Cite
|
Sign up to set email alerts
|

A General Protein Unfolding‐Chemical Coupling Strategy for Pure Protein Hydrogels with Mechanically Strong and Multifunctional Properties

Abstract: Protein-based hydrogels have attracted great attention due to their excellent biocompatible properties, but often suffer from weak mechanical strength. Conventional strengthening strategies for protein-based hydrogels are to introduce nanoparticles or synthetic polymers for improving their mechanical strength, but often compromise their biocompatibility. Here, a new, general, protein unfolding-chemical coupling (PNC) strategy is developed to fabricate pure protein hydrogels without any additives to achieve bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 57 publications
1
49
0
Order By: Relevance
“…Supramolecular hydrogels with dynamic associations as physical cross-links are a class of soft materials with fascinating viscoelastic behaviors, when compared to hydrogels cross-linked by permanent covalent bonds. So far, numerous tough hydrogels have been developed by incorporating physical associations (e.g., van der Waals interactions, hydrogen bonds, ionic bonds, and coordination bonds). , These supramolecular hydrogels possess balanced properties, including high mechanical toughness, self-recovery, and good processability, which greatly broaden the applications of hydrogel materials in biomedical and engineering fields. Hydrogen bonds, as a prevalent non-covalent interaction, exist widely in living systems and play a fundamental role in life activities. A typical hydrogen bond is formed as X–H···Y, in which X and Y are the proton donor and acceptor, respectively . Generally, a singular hydrogen bond is recognized as a relatively weak interaction with the dissociation energy about 5–17 kJ/mol. , However, the cooperativity of hydrogen bonds can significantly enhance the strength to be robust associations, accompanying with the increase in dissociation energy .…”
Section: Introductionmentioning
confidence: 99%
“…Supramolecular hydrogels with dynamic associations as physical cross-links are a class of soft materials with fascinating viscoelastic behaviors, when compared to hydrogels cross-linked by permanent covalent bonds. So far, numerous tough hydrogels have been developed by incorporating physical associations (e.g., van der Waals interactions, hydrogen bonds, ionic bonds, and coordination bonds). , These supramolecular hydrogels possess balanced properties, including high mechanical toughness, self-recovery, and good processability, which greatly broaden the applications of hydrogel materials in biomedical and engineering fields. Hydrogen bonds, as a prevalent non-covalent interaction, exist widely in living systems and play a fundamental role in life activities. A typical hydrogen bond is formed as X–H···Y, in which X and Y are the proton donor and acceptor, respectively . Generally, a singular hydrogen bond is recognized as a relatively weak interaction with the dissociation energy about 5–17 kJ/mol. , However, the cooperativity of hydrogen bonds can significantly enhance the strength to be robust associations, accompanying with the increase in dissociation energy .…”
Section: Introductionmentioning
confidence: 99%
“…The stress–strain curves for the compression–relaxation cycle at the strain of 50% for hydrogels modified with different ratios of glyoxylic acid and BSA are shown in Figure 4 C. The maximum stress of the hydrogels at 50% showed similar trends with that of the absolute value of the zeta potential, further proving that the enhancement of mechanical strength was attributed to the surface charge modification of BSA ( Figure 4 D). Obvious hysteresis between the loading and unloading curves was observed for all the hydrogels due to the energy dissipation caused by protein unfolding [ 27 , 30 , 40 ]. Interestingly, the energy dissipation also exhibited the same trends as that of the absolute values of zeta potentials, probably due to the fact that strong electrical repulsion makes it easier to unfold the BSA proteins ( Figure S5B ).…”
Section: Resultsmentioning
confidence: 99%
“…250,[288][289][290] To address these problems, solid-state double-network (DN) HEs, which are composed of two independent and interpenetrating polymer networks, have been developed for enhancing mechanical strength and flexibility. 243,[291][292][293][294][295][296][297][298][299] The SCs with superior mechanical stretchability (up to 1000%) and excellent self-healing behavior under either heating or light treatment were reported by Li et al, 243 where the SCs were incorporated with a multifunctional hydrogel polyelectrolyte with copolymerization of 2-acrylamido-2-methylpropane sulfonic acid and N,N-dimethylacrylamide. Lin et al 291 reported a novel Li 2 SO 4 -containing agarose/polyacrylamide double-network (Li-AG/PAM DN) hydrogel electrolyte, which was synthesized by a heating-cooling and subsequent radiation-induced polymerization and cross-linking process.…”
Section: Double-network Gel Electrolytesmentioning
confidence: 96%
“…However, the single‐component solid‐state HEs exhibited poor mechanical strength and flexibility 250,288–290 . To address these problems, solid‐state double‐network (DN) HEs, which are composed of two independent and interpenetrating polymer networks, have been developed for enhancing mechanical strength and flexibility 243,291–299 . The SCs with superior mechanical stretchability (up to 1000%) and excellent self‐healing behavior under either heating or light treatment were reported by Li et al, 243 where the SCs were incorporated with a multifunctional hydrogel polyelectrolyte with copolymerization of 2‐acrylamido‐2‐methylpropane sulfonic acid and N , N ‐dimethylacrylamide.…”
Section: Polymer‐based Solid‐state Electrolytes For Flexible Scsmentioning
confidence: 99%